Brown v. Board of Education - Tackach, James (San Diego, CA : Lucent Books, 1998)
Provides a historical overview of the case that desegregated public education in the United States.
Includes bibliographical references (p. 104-105) and index.
Keywords: Brown, Oliver, -- 1918-1961 -- Trials, litigation, etc. -- Juvenile literature; Brown, Oliver, -- 1918-1961 -- Trials, litigation, etc; Topeka (Kan.). -- Board of Education -- Trials, litigation, etc. -- Juvenile literature; Segregation in education -- Law and legislation -- United States -- Juvenile literature; Segregation in education -- Law and legislation; African Americans -- Civil rights